TRANSPOSITION AND EXPRESSION OF GEP GENE IN THE GENOME OF Vibrio harveyi TO MONITOR ITS ADHERENCE IN SHRIMP LARVAE - Antonius Suwanto (SEAMEO BIOTROP, 2006)
Expression of green fluorescent protein encoded by GFP gene in Vibrio harveyi was investigated to understand the ability of the gene as a molecular marker for adherence of this pathogenic Vibrio in shrimp larvae. The GFP gene was inserted into pUC18Not and pUTmini-Tn5 to generate a recombinant plasmid pWGO2 and pWGO3, respectively, which was transferred into the three isolates of V. harveyi employing diparental mating. Recombinant E. coli carrying pWGO2 and pWGO3 resulted in green-fluorescent colonies and cells due to the production of GFP. However, al1 of mini-Tn5, including mini-Tn5-gfp were not successful1y transferred to V. harveyi. Therefore, we used mini-Tn10 (pLOFKm-gfp) for inserting of gfp gene into V. harveyi genome. Although we could obtain relatively high (l0 pangkat -8) transconjugans employing Tn10, only one of Tnl0 derived isolate of V. harveyi G3 (G3-Tn1Ogfp) showed gfp expression and was further employed for adherence assay. Fluorescent 03-TnlOgfp cells could be observed inside the digestive tract of shrimp larvae and could be distinguished from vibrio that naturally exist in shrimp larvae.